Propriedades físico-mecânicas de fibrocimento reforçado com fibras de eucalipto tratadas termicamente - Silva, Danillo Wisky (2015)
The objective of this study was to evaluate the effect of different reinforcement levels of eucalyptus fibers in the physical-mechanical properties of fiber cements, as well as the effect of a thermal pretreatment of the fibers in the physical-mechanical properties of the fiber cements, both produced by extrusion process. For the production of fiber cements were used CPV-ARI Portland cement, agricultural lime, fibers Eucalyptus spp., Hidroxipropelmetilcellulose (HPMC) and carboxylic polyether (ADVA). The treatments were divided into two stages, the first stage was to evaluate different reinforcement levels with fibers (0, 1, 2, 3, 4 and 5%) to replace the cement (68 to 63%) in the second phase was rated different temperatures (0; 140; 170; 200 and 230 ° C) heat treatment of the eucalyptus fibers was used 3% reinforcing fiber (set after analysis of the results of phase) and 65% cement. For both phases of this work were added to 30% mixture of lime, and 1% HPMC 1% ADVA. The relative water: cement ratio was approximately 0.40. The samples (10 replicates per treatment) were prepared by the extrusion process. In the first phase there was a significant difference for the water absorption properties (WA), porosity void (PV) and specific energy, where the fiber cements with 4 to 5% fibers had the highest values were also no significant differences in the properties of apparent density (AD), modulus of rupture (MOR), modulus of elasticity (MOE) and the limit of proportionality (LOP), where the fiber cements 4 and 5% were smaller values. In the second phase of this study were significant differences only for the PV and AD properties where the fiber cements reinforced with fibers treated with 200 and 230 ° C obtained the highest values. In general, the use of eucalyptus fibers as reinforcements in fiber cements proved feasible at different levels evaluated reinforcement. Heat treatments changed the chemical composition of the fiber influencing the PA and DA property, however one should emphasize the need to assess the effect of these treatments on the durability of fiber cements, question this key to enable the use of new reinforcing materials.